Omplacering av katt i Sverige : via Blocket.se - Lust, Alva (SLU/Dept. of Animal Environment and Health (until 231231), 2021)
The amount of homeless cats on this planet is a problem for many countries in the world, including Sweden with an estimated 100 000 homeless cats. It is not obliged to register cats in Sweden which makes it easy to buy, sell and own a cat. That increases the risks for impulsive purchases and cats in need of rehoming and the possibility of them ending up homeless. Common reasons for leaving cats to shelters include allergies and homelessnes. This study aimed to find out what the need for rehoming cats was in Sweden, what reasons there were behind it and if advertisements for rehoming cats contain what is needed to contribute to the cat’s future welfare. Online advertisements were gathered every day from a swedish online marketplace called Blocket.se during a period of 10 weeks, between February and April. Results showed that 1470 cats needed rehoming through 1221 advertisements and that the most common reasons put in them for rehoming were allergies, that the cat needs another environment and that there are problems between the cat and other animals in the household. A description of the cat’s needs did not occur often and requirements for the new owner or household occurred in a fourth of the online advertisements. A worrying result was that the majority of cats from the advertisements were only 2 years old or less which suggests that people have a lack of knowledge regarding cat’s behaviour and needs. This study may contribute to raising awareness of the amount of cats in Sweden that need to find a new home and encourage people to adopt instead of shop.